2012
DOI: 10.1038/nchem.1528
|View full text |Cite
|
Sign up to set email alerts
|

A divergent approach to the synthesis of the yohimbinoid alkaloids venenatine and alstovenine

Abstract: The yohimbinoid alkaloids have received considerable attention from the synthetic community due to their interesting chemical structures and varied biological activity. Although there have been several elegant syntheses of certain members of this group of alkaloids, a truly unified approach has yet to be developed. In short, general approaches to this compound class have been hampered by a lack of complete control in setting the C(3) stereocenter at a late stage. Herein, we report that a functionalized hydrind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
31
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 40 publications
(48 reference statements)
0
31
0
Order By: Relevance
“…We previously observed that the combination of Lewis acid and Brønsted base increased the rate of Pictet-Spengler cyclisation in the six-membered ring system. [11] Unfortunately, scandium, indium, and lanthanum did not significantly change the diastereomeric ratio (Table 2) but did increase the rate of the reaction (entries [3][4][5], with scandium triflate showing marginally better activity than the other two. Temperature can have a dramatic effect on stereoselectivity by favouring the kinetic product and temperature-dependent changes in the diastereoselectivity of the standard Pictet-Spengler reaction of tryptamine with enantiopure aldehydes is known.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…We previously observed that the combination of Lewis acid and Brønsted base increased the rate of Pictet-Spengler cyclisation in the six-membered ring system. [11] Unfortunately, scandium, indium, and lanthanum did not significantly change the diastereomeric ratio (Table 2) but did increase the rate of the reaction (entries [3][4][5], with scandium triflate showing marginally better activity than the other two. Temperature can have a dramatic effect on stereoselectivity by favouring the kinetic product and temperature-dependent changes in the diastereoselectivity of the standard Pictet-Spengler reaction of tryptamine with enantiopure aldehydes is known.…”
Section: Resultsmentioning
confidence: 99%
“…d C (obtained from HMBC and HSQC) (100 MHz, [D6]DMSO) 148. 5,59.9,48.9,40.6,27.2,23.2,16.3. m/z (HRMS) …”
Section: Lewis Acid-catalysed Pictet-spengler Cyclisation Of 4 (Free mentioning
confidence: 99%
See 3 more Smart Citations